ANALISIS KEBERLANJUTAN USAHA MELALUI STRATEGI PEMASARAN 4.0 DALAM MENINGKATKAN PANGSA PASAR UNTUK KEUNGGULAN BERSAING (STUDI KASUS PADA USAHA IKANKOE DI KOTA KUPANG) - Zainal Arifin Pua Geno; Chairul Pua Tingga (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
Ikankoe's business is the first online fish sales business in Kupang City, during the Covid-19 pandemic Ikankoe's sales volume increased sharply, because community activities were restricted by the government, so that in fulfilling food needs, one of which was fish, people bought online, but after the Covid-19 pandemic the sales volume of Ikankoe's business decreased, because fish sales activities in markets in Kupang City began to normalize again. The purpose of this study is to determine the sustainability of Ikankoe's business through marketing strategy 4.0 for competitive advantage. This research uses a qualitative research method using narrative analysis. The analysis tool used in this research is Nvivo 12 Plus sortware. The results showed that Ikankoe's effort to maintain the sustainability of Ikankoe's business is to change its business activities from the concept of sales to marketing, where the main key to the marketing concept is to achieve organizational goals by determining the needs and desires of target market consumers and providing satisfaction to consumers more effectively and efficiently than competitors, Since its establishment, Ikankoe has determined its market segmentation, namely smartphone users. Marketing strategy 4.0 is the right strategy for the sustainability of Ikankoe's business through websites and Instagram and supported by strategic offline store locations that are able to increase sales in the post-covid-19 pandemic era. Ikankoe's brand has very good positioning in the minds of consumers as an online fish marketing stall in Kupang City. Ikankoe also innovates in the product aspect through a product diversification strategy, then in the service aspect Ikankoe makes it easy for consumers to access the website and make transactions to purchase products (orders and payments) and respond quickly to consumers.